Improving the Effectiveness of Psychological Interventions for Depression and Anxiety in Cardiac Rehabilitation: PATHWAY—A Single-Blind, Parallel, Randomized, Controlled Trial of Group Metacognitive Therapy. Issue 1 (21st June 2021) - Wells, Adrian; Reeves, David; Capobianco, Lora; Heal, Calvin; Davies, Linda; Heagerty, Anthony; Doherty, Patrick; Fisher, Peter
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: Depression and anxiety in cardiovascular disease are significant, contributing to poor prognosis. Unfortunately, current psychological treatments offer mixed, usually small improvements in these symptoms. The present trial tested for the first time the effects of group metacognitive therapy (MCT; 6 sessions) on anxiety and depressive symptoms when delivered alongside cardiac rehabilitation (CR). Methods: A total of 332 CR patients recruited from 5 National Health Service Trusts across the North-West of England were randomly allocated to MCT+CR (n=163, 49.1%) or usual CR alone (n=169, 50.9%). Randomization was 1:1 via minimization balancing arms on sex and Hospital Anxiety and Depression Scale scores within hospital site. The primary outcome was Hospital Anxiety and Depression Scale total after treatment (4-month follow-up). Secondary outcomes were individual Hospital Anxiety and Depression Scales, traumatic stress symptoms, and psychological mechanisms including metacognitive beliefs and repetitive negative thinking. Analysis was intention to treat. Results: The adjusted group difference on the primary outcome, Hospital Anxiety and Depression Scale total score at 4 months, significantly favored the MCT+CR arm (–3.24 [95% CI, –4.67 to –1.81], P <0.001; standardized effect size, 0.52 [95% CI, 0.291 to 0.750]). The significant difference was maintained at 12 months (–2.19 [95% CI, –3.72 to –0.66], P =0.005; standardized effect size, 0.33 [95% CI, 0.101 to 0.568]). The intervention improved outcomes significantly for both depression and anxiety symptoms when assessed separately compared with usual care. Sensitivity analysis using multiple imputation of missing values supported these findings. Most secondary outcomes favored MCT+CR, with medium to high effect sizes for psychological mechanisms of metacognitive beliefs and repetitive negative thinking. No adverse treatment-related events were reported. Conclusions: Group MCT+CR significantly improved depression and anxiety compared with usual care and led to greater reductions in unhelpful metacognitions and repetitive negative thinking. Most gains remained significant at 12 months. Study strengths include a large sample, a theory-based intervention, use of longer-term follow-up, broad inclusion criteria, and involvement of a trials unit. Limitations include no control for additional contact as part of MCT to estimate nonspecific effects, and the trial was not intended to assess cardiac outcomes. Nonetheless, results demonstrated that addition of the MCT intervention had broad and significant beneficial effects on mental health symptoms. Registration: URL: https://www.clinicaltrials.gov ; Unique identifier: ISRCTN74643496.